KOTA DEPOK: SEJARAH DAN HARI JADINYA - Rida Fadilah; Putri Irayani; Ichwan Azhari; Samsidar Tanjung (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study discusses issues regarding the history and anniversary of the city of Depok. It cannot be denied that the city of Depok has a long history because it has existed since the 17th century. This can be seen from the Dutch colonial buildings located in the city of Depok, but now they have changed their function and have been destroyed. However, the city of Depok developed into a modern city and left its identity as a city with a million history in it. The historical aspects inherent in Depok are gradually being eroded as the function of heritage buildings has changed into commercial facilities such as kiosks and shops. This study aims to describe the history of the founding of the city of Depok. In addition, it also examines the anniversary of the city of Depok which should be. This study uses a qualitative approach with library research methods. This library research was conducted by reading and analyzing books, journals, and various literature reading materials which were then outlined in this paper. This study found the fact that Depok is a city that is hundreds of years old and keeps long historical records so that it is not much different from the cities of Bandung and the cities of Jakarta.